Factors affecting 137Cs radioactivity and water-to-body concentration ratios of fish in river and pond environments near the Fukushima Dai-ichi Nuclear Power Plant. (March 2023) - Wada, Toshihiro; Hinata, Akinori; Furuta, Yuma; Sasaki, Keiichi; Konoplev, Alexei; Nanba, Kenji
Abstract: To elucidate 137 Cs contamination levels and mechanisms of fish inhabiting river and pond environments near the Fukushima Dai-ichi Nuclear Power Plant, 137 Cs activity concentrations in fish (15 species, n = 164) and water collected from Maeda River (3.3–8.9 km from the plant) and Shimofukazawa Pond (2.9 km) in 2017 were analyzed. Also, an 8-week rearing experiment using Japanese dace Pseudaspius hakonensis fed on non-contaminated pellets and the pond water (mean 137 Cs concentration of 2.0 Bq/L) was conducted to evaluate 137 Cs accumulation from water to fish. The 137 Cs concentrations in Japanese dace, the only species collected throughout five sampling sites from estuarine to upstream areas in Maeda River, were found to be correlated with ambient air dose rates and fish size, exhibiting large variations (16.5–2.6×10 3 Bq/kg-wet). By contrast, dissolved 137 Cs in river waters increased from the upper to lower course (0.025–0.28 Bq/L), which caused large variations of the water-to-body concentration ratio (CR) in Japanese dace (60.0–35700 L/kg-wet). These CRs (geometric mean of 3670 L/kg-wet) were much higher than the steady-state CR of reared fish (9.7 L/kg-wet), indicating that river fish uptake 137 Cs mainly from prey items from aquatic and riparian zones, rather than from water. Statistically significant negative correlations between K + concentrations in water and river fish CRs were detected, resulting in the decreasing trend of CRs from upstream to estuarine areas. These results suggest that the large heterogeneity of air dose rates, K + concentration, and estuarine processes in brackish water habitats, in association with the feeding habit and size effect in fish, can engender wide variation of 137 Cs concentrations and CRs of river fish along a river course. In contrast, 137 Cs concentrations in pond fish (4.3–14.6 kBq/kg-wet) were higher than in river fish. The CRs of pond fish were constantly high but the range was smaller (1010–3440 L/kg-wet) with larger values in fish of higher trophic levels. These findings suggest that biomagnification within a pond was inferred as the main cause of 137 Cs contamination of pond fish. Highlights: 137 Cs in fish and waters near the Fukushima Dai-ichi Nuclear Plant was analyzed. Higher water-to-body concentration ratios (CRs) of wild fish are attributable to 137 Cs food uptake. Air dose rates of river sides and estuarine processes affect river fish 137 Cs and CRs. K + concentrations in water and river fish CRs correlated negatively. Biomagnification of 137 Cs through food webs is pronounced for pond fish.